2010
DOI: 10.1186/1757-1146-3-10
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in symptoms and signs in the forefoot of patients with rheumatoid arthritis treated with anti‐TNF therapy

Abstract: BackgroundInhibition of tumour necrosis factor (TNF) is an effective way of reducing synovitis and preventing joint damage in rheumatoid arthritis (RA), yet very little is known about its specific effect on foot pain and disability. The aim of this study was to evaluate whether anti-TNF therapy alters the presence of forefoot pathology and/or reduces foot pain and disability.MethodsConsecutive RA patients starting anti-TNF therapy (infliximab, etanercept, adalimumab) were assessed for presence of synovial hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…We hypothesized that, in patients who have RA, the increased prevalence of FFB may be related to increased inflammation. This concurs with other investigators who have suggested that the synovium, which lines the otherwise inconspicuous intermetatarsal (IM) anatomical bursae, becomes hypertrophied as a consequence of excessive disease activity (). Conversely, other investigators have hypothesized that adverse mechanical pressure and shearing forces may result in the accumulation of interstitial fluid within the subcutaneous tissues, often termed adventitial bursae ().…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…We hypothesized that, in patients who have RA, the increased prevalence of FFB may be related to increased inflammation. This concurs with other investigators who have suggested that the synovium, which lines the otherwise inconspicuous intermetatarsal (IM) anatomical bursae, becomes hypertrophied as a consequence of excessive disease activity (). Conversely, other investigators have hypothesized that adverse mechanical pressure and shearing forces may result in the accumulation of interstitial fluid within the subcutaneous tissues, often termed adventitial bursae ().…”
Section: Introductionsupporting
confidence: 91%
“…All US scans were performed after completion of a clinical assessment, as per the standardized protocol for the study. The primary study outcome, the presence of FFB, was determined for all participants using a predetermined US scanning protocol for the forefoot region (). Both forefeet were imaged in all participants from plantar and dorsal approaches, in longitudinal and transverse scanning planes, using 8–16‐MHz and 5–10‐MHz linear array transducers, and imaging was completed prior to the assessment of mechanical foot characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…The intermetatarsal bursae are visible at US evaluation when pathologically inflamed as the accumulation of fluid (anechoic area that is compressible) surrounded by thickened, hypoechoic walls (due to the hypertrophy of the synovial layer), that bulges more than 1 mm under the metatarsal head level. The US examination of submetatarsal bursae shows a hypoechoic/anechoic or heterogenous fluid accumulations located at the level of submetatarsal fat tissue [6,[31][32][33][34][35]. The intermetatarsal bursae are located just above the deep transverse metatarsal ligament, never extending below this structure.…”
Section: Metatarsophalangeal (Mtp) Joints Synovial Hypertrophy and Efmentioning
confidence: 99%
“…Subclinical involvement of the feet and ankles joints (with the aspect of synovitis in US examination), frequently overlooked by clinicians, also impairs feet functionality and patients' quality of life [5]. Foot and ankle disability and pain in RA patients significantly improve after initiation of biological therapy [6] but this is valuable if the treatment is initiated before the advance/irreversible lesions appeared.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation of the synovial membrane is a hallmark of the disease, with the disease eventually progressing to cartilage and osseous degradation. There is no known cure, however therapeutic treatments are available and recent advances in the imaging of the disease and associated inflammation have allowed earlier diagnosis and intervention [3,4], with the possibility for increased mobility and quality of life for patients through disease management [5-7]. …”
Section: Introductionmentioning
confidence: 99%